2022
DOI: 10.3389/fimmu.2022.773264
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor Antigens and Immune Subtypes of Glioblastoma for mRNA Vaccine Development

Abstract: The use of vaccines for cancer therapy is a promising immunotherapeutic strategy that has been shown to be effective against various cancers. Vaccines directly target tumors but their efficacy against glioblastoma multiforme (GBM) remains unclear. Immunotyping that classifies tumor samples is considered to be a biomarker for immunotherapy. This study aimed to identify potential GBM antigens suitable for vaccine development and develop a tool to predict the response of GBM patients to vaccination based on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 86 publications
1
25
0
Order By: Relevance
“…PLB1 (phospholipase B1) is a secreted membrane-associated phospholipase that is involved in choline metabolism in tumors [ 32 ]. PLB1 mutation was reported to be associated with poor survival in non-small cell lung cancer and glioblastoma multiform [ 33 , 34 ]. As shown in Table 2 , our results demonstrated that the genetic mutations of these genes mentioned above ( CDH1 , ARID1A , FAT4 , KMT2C , TP53 , KMT2D , MACF1 , and PLB1 ) were associated with the down regulation of the associated protein function, which may be involved in the up-regulation or down-regulation in the mechanism of cancer developing.…”
Section: Discussionmentioning
confidence: 99%
“…PLB1 (phospholipase B1) is a secreted membrane-associated phospholipase that is involved in choline metabolism in tumors [ 32 ]. PLB1 mutation was reported to be associated with poor survival in non-small cell lung cancer and glioblastoma multiform [ 33 , 34 ]. As shown in Table 2 , our results demonstrated that the genetic mutations of these genes mentioned above ( CDH1 , ARID1A , FAT4 , KMT2C , TP53 , KMT2D , MACF1 , and PLB1 ) were associated with the down regulation of the associated protein function, which may be involved in the up-regulation or down-regulation in the mechanism of cancer developing.…”
Section: Discussionmentioning
confidence: 99%
“…Both such biomarkers were upregulated in mesenchymal compared to classical phenotype. Previously, CD300E was detected as the receptor stimulating monocyte activity and was even suggested as a potential antigen for an RNA vaccine against GBM [35,36].…”
Section: Gene Biomarkersmentioning
confidence: 99%
“…In recent years, accumulating attention has been paid by scholars worldwide, to the development of the cancer vaccine, which attempts to enhance the patients’ immunity against cancerous cells [ 8 ]. The discovery of tumor associated antigens (TAAs) represents one of the major challenges in the design of a vaccine, and several studies have introduced new ideas to the identification of TAAs [ 9 , 10 , 11 ]. In the family of cancer vaccines, compared to other members, messenger RNA (mRNA) vaccines possess some unique advantages such as: synchronously eliciting the humoral and cell immunity, without a risk of integration into the nuclear genome and encoding more epitopes to be presented by antigen presenting cells (APCs) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%